Democratic Republic of the Congo : Poverty Reduction Strategy Paper-Progress Report-Joint Staff Advisory Note. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Congo's first full Poverty Reduction and Growth Strategy underpinned the economic policy during a particularly challenging transitional period. The difficulty is in implementing the program in a rapidly evolving institutional environment. Developments during recent years demonstrate Congo's capacity for growth and poverty alleviation if the right incentives are provided. Developments during the last year also indicate the government's commitment to address the key issues, even in the face of significant political challenges. The government's response to short-term concerns builds on a compelling vision of long-term development.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet